Prospective and Territorial Planning. Lessons learned from the process in the periurban area of Corral de Bustos Ifflinger (Córdoba, Argentina) - Madoery, Ormando Aníbal (2023)
The purpose of the territorial prospective study was to build knowledge related to the future of the peri-urban area of ??Corral de Bustos Ifflinger, through a systematic and participatory process to combine visions in the medium and long term, with the aim of guiding the decisions that have to be made. in the present and mobilize joint actions to build the desired future. The proposal sought, from interdisciplinary work, to address the peri-urban territory, reaching the latter as a space for conflicts, to establish future guidelines that help a more sustainable territorial ordering. Thus, the National Institute of Agricultural Technology, the Center for Environmental Land Management Studies of the National University of Villa María and the Municipality of Corral de Bustos Ifflinger implemented the prospective methodology, with interviews, background checks and three workshops. participatory work that resulted in the incorporation of topics that are of interest in the future agenda of the town.